Tuning the Molecular Structure of Corroles to Enhance the Antibacterial Photosensitizing Activity - Edwin J. Gonzalez Lopez; Sol R. Martínez; Virginia Aiassa; Sofía C. Santamarina; Rodrigo E. Domínguez; Edgardo N. Durantini; Daniel A. Heredia (Pharmaceutics, 2023)
The increase in the antibiotic resistance of bacteria is a serious threat to public health. Photodynamic inactivation (PDI) of micro-organisms is a reliable antimicrobial therapy to treat a broad spectrum of complex infections. The development of new photosensitizers with suitable properties is a key factor to consider in the optimization of this therapy. In this sense, four corroles were designed to study how the number of cationic centers can influence the efficacy of antibacterial photodynamic treatments. First, 5,10,15-Tris(pentafluorophenyl)corrole (Co) and 5,15-bis(pentafluorophenyl)-10-(4-(trifluoromethyl)phenyl)corrole (Co-CF3) were synthesized, and then derivatized by nucleophilic aromatic substitution with 2-dimethylaminoethanol and 2-(dimethylamino)ethylamine, obtaining corroles Co-3NMe2 and Co-CF3-2NMe2, respectively. The straightforward synthetic strategy gave rise to macrocycles with different numbers of tertiary amines that can acquire positive charges in an aqueous medium by protonation at physiological pH. Spectroscopic and photodynamic studies demonstrated that their properties as chromophores and photosensitizers were unaffected, regardless of the substituent groups on the periphery. All tetrapyrrolic macrocycles were able to produce reactive oxygen species (ROS) by both photodynamic mechanisms. Uptake experiments, the level of ROS produced in vitro, and PDI treatments mediated by these compounds were assessed against clinical strains: methicillin-resistant Staphylococcus aureus and Klebsiella pneumoniae. In vitro experiments indicated that the peripheral substitution significantly affected the uptake of the photosensitizers by microbes and, consequently, the photoinactivation performance. Co-3NMe2 was the most effective in killing both Gram-positive and Gram-negative bacteria (inactivation > 99.99%). This work lays the foundations for the development of new corrole derivatives having pH-activable cationic groups and with plausible applications as effective broad-spectrum antimicrobial photosensitizers.